Dialysis Access Cases : Practical Solutions to Clinical Challenges - Yevzlin, Alexander S.; Asif, Arif; Redfield III, Robert R.; Beathard, Gerald A. (Springer International Publishing : Imprint: Springer, 2017)
Moving beyond the science of hemodialysis access, this collection of clinical cases covers procedural and practical aspects of arteriovenous fistula, arteriovenous graft, dialysis catheter, draining veins, central veins, arterial interventions and hand ischemia. World experts in the disciplines of interventional nephrology, interventional radiology and surgery offer creative visions of their practice and provide insights on topics from routine access creation to advanced novel techniques. Dialysis Access Cases presents solutions to problems encountered in practice while capturing the art of this medical discipline and challenging procedure.
Keywords: Medicine.; Interventional radiology.; Nephrology.; Vascular surgery.; elektronické knihy; electronic books